Soft i-Open Sets in Soft Bi-Topological Spaces - Sabih Askandar; Beyda S. Abdullah; Luma Khaleel (Al-Qadisiyah Journal of Pure Science, 2023)
In our study we introduced soft i-open sets and soft i-star-generalized-w-closed sets in soft bi-topological spaces, , using the notion of soft i-open sets in soft-topological-space, . We besides that give examples to clarify these relationships while presenting some essential characteristics and relationships between various groups of sets. Besides that we studied the property of soft bi-topologically extended and non-soft bi-topologically extended of soft i-open sets in soft bi-topological spaces by proofs and examples.